Pemanfaatan Aplikasi Power Point dalam Pembelajaran Pendidikan Agama Islam dalam Peningkatan Motivasi Belajar siswa di SMP PAB 1 Klumpang - Muhammad Arya Arjuna; Muhammad Irvan Alwi; Hasrian Rudi Setiawan (Maslahah: Jurnal Pengabdian Masyarakat, 2021)
The purpose of implementing the Community Partnership Program (PKM) is to provide knowledge and skills to create and use attractive power point applications to teachers at SMP PAB 1 Klumpang. The method used in this activity is the direct method, where the team directly provides training to the participants, and each participant with their laptop device takes steps to use the power point application taught by the presenter/trainer. The results achieved from this program are 82% of the participants are able to make and use the power point applications well that are trained to them, and can apply them in carrying out learning activities.Keywords: Power Point, Learning, Islamic Religious Education